Implementasi pendidikan multikurtural melalui pendekatan nilai luhur budaya dan pancasila untuk membangun karakter mahasiswa dalam meghadapi arus globalisasi - Muhammad Misbahudholam A.R. (Universitas Negeri Malang, 2016)
Globalization is indeed very strongly felt in every aspects of life of society, nation and state. The joints are ediologi, political, economic, social, cultural, defense and security. The fade of nationalism and solidarity is one of the diseases that are suffered by children of this country. This factor is also the background for the emergence of awareness of the importance of education implementation multikurtural in building character/good manners. Characters based on a multicultural nation in accordance with the motto